General physics 1 - David, Oliver M. (Makati City : Diwa Learning System, Inc., 2020)
"Learning is best achieved if it develops positive values. The reflection activities in this textbook will guide you in emphasizing your appreciation of the concepts of physics and their application and relevance to your personal lives. This textbook is divided into two units, and each unit is further divided into modules. Each module will guide you in using online resources so that you will have an expansive horizon in exploring the principles of physics. Learning beyond the walls of your classroom will provide you with limitless opportunities to explore and discover as much as you can and at your own pace."
Includes bibliography.
English text.
Keywords: Physics -- Study and teaching